Tolerance to Dizziness Intensity Increases With Age in People With Chronic Dizziness - Prell, Tino; Mendorf, Sarah; Axer, Hubertus (Frontiers in Neurology, 2022)
Background: Dizziness is a common complaint in older adults. To know which factors are instrumental in enabling patients with chronic dizziness to tolerate their symptoms to a certain degree in everyday life, can help to develop tailored therapies. Methods: Data from 358 patients with chronic dizziness and vertigo who had attended a multimodal daycare treatment program were recorded. Data included sociodemographic parameters, dizziness-related characteristics, the Vertigo Symptom Scale (VSS), and the Hospital Anxiety and Depression Scale (HADS). Descriptive statistics, elastic net regression, and mediation analysis were used. Results: A higher tolerance of dizziness was associated with higher age, higher intensity of dizziness, lower burden of dizziness, higher HADS depression, structural reason of dizziness (type), permanent dizziness, absence of attacks, and longer disease duration. In contrast, younger persons with attack-like dizziness reported to tolerate less dizziness. Age had a significant direct effect on tolerance (72% of the total effect) and a significant indirect effect via intensity on tolerance (28% of the total effect) in the mediation analysis Conclusion: It can only be speculated that negative stereotypes about age-related complaints may play a role in this. Why older people tolerate more dizziness and to what extent this may contribute to lower health care utilization needs to be investigated in further studies.